Implementation Quality: Implications for Intervention and Translational Science. Issue 2 (22nd November 2018) - Norris, Anne E.; Matsuda, Yui; Altares Sarik, Danielle; Pettigrew, Jonathan
Abstract: Purpose: Implementation quality (IQ), a critical concept for translational science, measures the discrepancy between an intervention's intended design and its implementation. Quantifying the impact of IQ on intervention outcomes informs efforts to improve intervention translatability. The purpose of this article is to define and describe IQ and its dimensions (content adherence, quality of delivery, and engagement) with a focus on individualized interventions being delivered in research and practice settings. Approach: We apply IQ concepts from intervention science in two contexts: (a) an intervention currently being investigated in an efficacy trial, and (b) a practice situation involving the application of evidence‐based practice guidelines during clinic visits. IQ measurement approaches are presented using a study protocol, progress notes, interdisciplinary meeting notes, or clinical guidelines, depending upon whether the intervention is delivered during a research study or a clinical encounter. Conclusions: The investigators describe the necessary infrastructure and support for capturing IQ data and the subsequent complexities and challenges of collecting, measuring, and analyzing these data. Understanding IQ is critical to advancing translational science. Such understanding informs application of appropriate IQ measures, and promotes effective translation of evidence‐based interventions into practice. Policy changes are needed to promote IQ assessment to ensure high‐quality clinical encounters during which interventions are effectively delivered. Clinical Relevance: In both research and practice settings, the conceptualization and measurement of IQ will improve patient outcomes by advancing translational science and integrating evidence‐based interventions into nursing practice.